Lipid peroxidation and tyrosine nitration in traumatic brain injury: Insights into secondary injury from redox proteomics. Issue 12 (14th October 2016) - Butterfield, D. Allan; Reed, Tanea T.
Abstract : Traumatic brain injury (TBI) is a spontaneous event in which sudden trauma and secondary injury cause brain damage. Symptoms of TBI can range from mild to severe depending on extent of injury. The outcome can span from complete patient recovery to permanent memory loss and neurological decline. Currently, there is no known cure for TBI; however, immediate medical attention after injury is most beneficial for patient recovery. It is a well‐established concept that imbalances in the production of reactive oxygen species (ROS), reactive nitrogen species (RNS), and native antioxidant mechanisms have been shown to increase oxidative stress. Over the years, proteomics has been used to identify specific biomarkers in diseases such as cancers and neurological disorders such as Alzheimer disease and Parkinson disease. As TBI is a risk factor for a multitude of neurological diseases, biomarkers for this phenomenon are a likely field of study in order to confirm diagnosis. This review highlights the current proteomics studies that investigated excessively nitrated proteins and those altered by lipid peroxidation in TBI. This review also highlights possible diagnostic measures and provides insights for future treatment strategies.